Special issue on online misogyny. Issue 4 (4th July 2018) - Ging, Debbie; Siapera, Eugenia
Abstract: This special issue seeks to identify and theorise the complex relationships between online culture, technology and misogyny. It asks how the internet's anti-woman spaces and discourses have been transformed by the technological affordances of new digital platforms, and whether they are borne of the same types of discontents articulated in older forms of anti-feminism, or to what extent they might articulate a different constellation of social, cultural and gender-political factors. This collection of work is intended to lend focus and cohesion to a growing body of research in this area; to map, contextualise and take stock of current frameworks, making scholars aware of one another's work and methodologies, and hopefully forging new interdisciplinary collaborations and directions for future work. Crucially, we move beyond the Anglophone world, to include perspectives from countries which have different gender-political and technological landscapes. In addition to mapping the new misogyny, several contributions also address digital feminist responses, evaluating their successes, limitations and impact on the shape of digital gender politics in future.